ANALYSIS OF TRAFFIC CONDITIONS AT THE BRZEZINSKA AND NOWOCHRZANOWSKA INTERSECTION IN MYSLOWICE (SILESIAN PROVINCE, POLAND) - Elżbieta MACIOSZEK; Damian LACH (Scientific Journal of Silesian University of Technology. Series Transport)
A detailed analysis of traffic conditions at the intersection allows us to obtain information about the efficiency of its operation. This type of analysis usually involves assessing the capacity and scale of the intersection and applying classical measures to assess its quality. In Poland, for this purpose, methods developed by the General Directorate for National Roads and Motorways are used to estimate the capacity of intersections without traffic lights, intersections with traffic lights, and roundabouts. The paper presents the results of the analysis of traffic conditions at the intersection of Brzezinska and Nowochrzanowska Streets, located in Myslowice (Silesian Province, Poland). The paper also examines the findings on traffic safety at this intersection.